State as a Subject of Investment Operations - Sushch, Olena (Law and innovations, 2022)
Problem setting. The research is focused on studying specific features of the legal status of the state as a subject of investment operations. The author of the article analyzes the norms of investment legislation reflecting the directions of state participation in investment operations. Analysis of resent researches and publications. Current scientific research mainly focuses on studying problematic aspects of legal regulation of certain types of investment operations. Modern theoretical and legal studies, where the subject matter is legal regulation of investment operations, pay insufficient attention to study specific features of the legal status of subjects of investment operations, in particular, the state’s legal status. Target of research is to study specific features of state’s legal status as a subject of investment operations. Аrticle’s main body. It has been established that the state can acquire different legal statuses in investment relations and can enter into investment relations of different legal nature. The state is one of the key subjects of investment operations, since it acts as: 1) a direct participant of investment operations – an investor or recipient of investment; 2) an entity that carries out state regulation of investment operations by: supporting the implementation of investment projects; administration of state investment projects; provision of preferential conditions for carrying out investment operations; control over the compliance with the loyalty of carrying out investment operations by all participants of investment relations; guaranteeing the rights of subjects of investment operations and as a guarantor in regard to the protection of investment; suspension or termination of investment operations by the decision of the state authority. The main functions of the state within investment operations have been determined – regulatory, security, and incentive. The regulatory function is aimed at regulating investment operations at the level of national and international legislation. The security function is aimed at protecting the rights and interests of subjects of investment operations by providing them with the guarantees under the investment legislation. The incentive function is aimed at establishing benefits and preferences for subjects of investment operations in order to attract investment into certain areas of investment operations. Conclusions and prospects for the development. The specific feature of the state’s legal status within investment operations is reflected through the possibility of entering into investment legal relations as an investor or recipient of investment and a regulator of investment relations and a guarantor for foreign investors. No subject of investment operations is endowed with such a wide range of powers as the state. On the basis of the above, it is worth stating that theoretical and legal approaches to studying the legal status of the state within investment operations have a fragmentary nature. The study of the legal status of the state as a subject of investment operations is a perspective direction for further scientific research.